2021
DOI: 10.1186/s12872-021-02376-w
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction with left main coronary artery ostial negative remodelling as the first manifestation of Takayasu arteritis: a case report

Abstract: Background Takayasu arteritis is a chronic inflammatory disease involving the aorta and its major branches. Acute myocardial infarction rarely but not so much presents in patients with Takayasu arteritis, and the preferable revascularization strategy is still under debate. Case presentation A 22-year-old female with Takayasu arteritis presented with acute myocardial infarction. Coronary angiography and intravenous ultrasound (IVUS) showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Intravascular US helps determine changes in the structure of the coronary artery wall and the presence of atherosclerotic plaques in coronary arteries [ 51 ]. Ishiyama et al [ 52 ] reported that IVUS showed that the three-layered structure of the intima, tunica media, and adventitia was not visible, and the vessel was concentrically thickened; unstable plaque and calcification were not seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravascular US helps determine changes in the structure of the coronary artery wall and the presence of atherosclerotic plaques in coronary arteries [ 51 ]. Ishiyama et al [ 52 ] reported that IVUS showed that the three-layered structure of the intima, tunica media, and adventitia was not visible, and the vessel was concentrically thickened; unstable plaque and calcification were not seen.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Sun et al [ 14 ] observed a history of MI in 8.9% of 15 patients. It is worth noting that MI can be the initial manifestation of TAK [ 41 , 51 ].…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…The proportion of coronary arteries involvement in patients with TA is about 9–10% [ 1 , 4 , 5 , 14 , 24 ]. TA mainly involves the ostia and proximal segment of coronary artery, showing the lesions of stenosis, occlusion or dilatation, which result in myocardial ischemia, angina pectoris or AMI [ 4 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently study reported HLA-B*52 allele was significantly associated with TA. However, the ostium involvement of the coronary arteries is caused by the extension of inflammation of the aortic root or ascending aorta [ 14 , 24 , 29 ], which leads to arterial wall remodeling, thickening, aneurysmal lesions, and stenosis or occlusion of the coronary vessel lumen [ 24 , 26 , 29 ]. In the acute inflammatory phase (active stage) of TA proinflammatory T-cell cytokines(such as TNF-α, IL-6 and IFN-γ, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The coronary artery is an important medium-sized vessel in the heart that may also be involved. Once the lesion is aggravated, thrombosis can develop, leading to MI and even death [21][22][23][24] . Even if immediate ischemia does not occur because of coronary artery occlusion, vessels that have been in amed in systemic vasculitides, such as TAK, show premature atherosclerosis, placing patients at risk for MI [25] .…”
Section: Discussionmentioning
confidence: 99%